Hubungan Antara Kesepian dengan Nomophobia pada Mahasiswa Perantau di Universitas Muhammadiyah Pontianak - Khavifi Miharni; Sri Nugroho Jati; Riszky Ramadhan (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Migrant students often face loneliness due to being away from family and their original environment, which can impact psychological well-being and trigger dependence on smartphones. This dependence can lead to nomophobia (no mobile phone phobia), characterized by anxiety and discomfort when separated from one’s phone. This study aims to examine the relationship between loneliness and nomophobia among migrant students at Universitas Muhammadiyah Pontianak. The research instruments used were the Loneliness Scale and the Nomophobia Scale, developed by the researcher based on the theoretical aspects of Cacioppo & Patrick (2008) and Yildirim & Correia (2015). This study employed a quantitative method with a correlational design and purposive sampling technique involving 100 migrant students. Data were analyzed using Pearson correlation through IBM SPSS Statistics 27. Results showed that most students fell into moderate to high categories for both variables. The correlation test yielded a coefficient of r = 0.359 with p = 0.000, indicating a significant positive relationship of moderate strength (based on correlation coefficient classification). These findings suggest that the higher the level of loneliness experienced, the higher the tendency toward nomophobia. Nevertheless, weaknesses were identified in the social connectedness aspect (loneliness) and the loss of convenience aspect (nomophobia). Therefore, follow-up measures such as coping strategies, strengthening social support, and digital literacy education are needed to help migrant students manage loneliness and more effectively prevent the negative impacts of nomophobia.